2020
DOI: 10.1002/da.23086
|View full text |Cite
|
Sign up to set email alerts
|

Biased distance estimation in social anxiety disorder: A new avenue for understanding avoidance behavior

Abstract: Objectives: People regulate their interpersonal space appropriately to obtain a comfortable distance for interacting with others. Socially anxious individuals are especially prone to discomfort from and fear of physical closeness, leading them to prefer a greater interpersonal distance from others. Previous studies also indicate that fear can enhance the threat-related elements of a threatening stimulus. For example, spider phobia is associated with estimating spiders as bigger and faster than they actually ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…They aptly note that social distancing precautions necessarily limit opportunities for exposure exercises for people with SA to face their fears by engaging in social interaction, thereby learning that such fears are often exaggerated. In one study conducted prior to the pandemic, individuals with SAD preferred more physical distance between themselves and others in social situations compared to individuals without SAD (Givon-Benjio et al, 2020), supporting the view that such individuals may have initially experienced increased comfort and an associated temporary reduction in anxiety when greater social distance became common practice at the onset of the coronavirus pandemic. However, recent self-report surveys have suggested that the COVID-19 pandemic has increased people's levels of SA and fears of negative evaluation overall, even despite the increases in physical distancing (Hawes et al, 2021;Ho & Moscovitch, 2021).…”
Section: Effects Of Additional Coronavirus-prevention Measures and Pre-existing Health Anxiety On Social Anxietymentioning
confidence: 94%
“…They aptly note that social distancing precautions necessarily limit opportunities for exposure exercises for people with SA to face their fears by engaging in social interaction, thereby learning that such fears are often exaggerated. In one study conducted prior to the pandemic, individuals with SAD preferred more physical distance between themselves and others in social situations compared to individuals without SAD (Givon-Benjio et al, 2020), supporting the view that such individuals may have initially experienced increased comfort and an associated temporary reduction in anxiety when greater social distance became common practice at the onset of the coronavirus pandemic. However, recent self-report surveys have suggested that the COVID-19 pandemic has increased people's levels of SA and fears of negative evaluation overall, even despite the increases in physical distancing (Hawes et al, 2021;Ho & Moscovitch, 2021).…”
Section: Effects Of Additional Coronavirus-prevention Measures and Pre-existing Health Anxiety On Social Anxietymentioning
confidence: 94%
“…In the context of physical distancing, a recent study found that individuals with SAD had biased distance estimation and tended to perceive strangers to be physically closer than they really were, but that this underestimation did not occur with familiar others, suggesting that greater physical distance may reduce perceptions of social threat for socially anxious individuals (Givon-Benjio et al, 2020). Another study using immersive virtual reality technology found participants with higher levels of social anxiety approached computer-generated avatars in a virtual setting more slowly and kept a larger distance (Rinck et al, 2010).…”
Section: Physical Distancingmentioning
confidence: 99%
“…Even though fears of negative evaluation have persisted during the pandemic, it is possible that socially anxious individuals feel that physical distancing measures help keep others at a safer social distance, thereby promoting greater affiliative attempts. There is clear support in the existing literature for the idea that greater physical distance may reduce perceptions of social threat for socially anxious individuals (Azriel, Lazarov, Segal, & Bar-Haim, 2020;Givon-Benjio, Oren-Yagoda, Aderka, & Okon-Singer, 2020;Kamalou et al, 2019;Rinck et al, 2010). They may be inconspicuously co-opting newly introduced social norms-such as communicating online, interacting from a physical distance, or conversing from behind a mask-as self-regulatory strategies, allowing them to remain concealed while conforming to societal expectations.…”
Section: Greater Control Over Self-presentationmentioning
confidence: 99%
“…Regarding social anxiety disorder, individuals seem to show low reward expectations about social interactions ( Clark and Wells, 1995 ), leading to the avoidance of such situations. As a significant cause and maintenance factor (e.g., Givon-Benjio et al, 2020 ), avoidance behavior will eventually result in social withdrawal and leave individuals with reward deficiency of social interactions.…”
Section: Introductionmentioning
confidence: 99%